Extensive scanning of the calpain-3 gene broadens the spectrum of LGMD2A phenotypes. Issue 9 (1st September 2005) - Piluso, G; Politano, L; Aurino, S; Fanin, M; Ricci, E; Ventriglia, V M; Belsito, A; Totaro, A; Saccone, V; Topaloglu, H; Nascimbeni, A C; Fulizio, L; et al.
Abstract : Background: The limb girdle muscular dystrophies (LGMD) are a heterogeneous group of Mendelian disorders highlighted by weakness of the pelvic and shoulder girdle muscles. Seventeen autosomal loci have been so far identified and genetic tests are mandatory to distinguish among the forms. Mutations at the calpain 3 locus (CAPN3) cause LGMD type 2A. Objective: To obtain unbiased information on the consequences of CAPN3 mutations. Patients: 530 subjects with different grades of symptoms and 300 controls. Methods: High throughput denaturing HPLC analysis of DNA pools. Results: 141 LGMD2A cases were identified, carrying 82 different CAPN3 mutations (45 novel), along with 18 novel polymorphisms/variants. Females had a more favourable course than males. In 94% of the more severely affected patient group, the defect was also discovered in the second allele. This proves the sensitivity of the approach. CAPN3 mutations were found in 35.1% of classical LGMD phenotypes. Mutations were also found in 18.4% of atypical patients and in 12.6% of subjects with high serum creatine kinase levels. Conclusions: A non-invasive and cost–effective strategy, based on the high throughput denaturing HPLC analysis of DNA pools, was used to obtain unbiased information on the consequences of CAPN3 mutations in the largest genetic study ever undertaken. This broadens the spectrum of LGMD2A phenotypes and sets the carrier frequency at 1:103.